Thermotolerant Probiotic—The Potential of Improving the Survivability of Beneficial Bacteria - Dorota Zielińska; Miłosz Krawczyk; Katarzyna Neffe-Skocińska (Fermentation)
Probiotics play a significant role in human nutrition. Heat stress is one of the most important factors leading to the inactivation and loss of viability of probiotics during their production. Therefore, there is a need to develop probiotics that can withstand higher temperatures during processing and storage. Thermotolerant bacteria are a group of microorganisms that survive at elevated temperatures due to the presence of active proteins in bacterial cells. In this review, the molecular mechanisms underlying the maintenance of the structural integrity of beneficial bacterial cells during heat stress are discussed. In addition, the possibilities of stimulating the resistance and adaptation of bacterial cells to high temperature are indicated. Finally, the possibilities of application of such solutions in the food industry are discussed. On the basis of a thorough literature review, it is concluded that it is still worth continuing the research on the mechanisms of resistance to heat stress in beneficial bacteria, because the molecular mechanisms of this process are not fully understood. It is believed that such knowledge could accelerate the development of the probiotic market in the future.